2022
DOI: 10.1039/d2tc03414j
|View full text |Cite
|
Sign up to set email alerts
|

Construction of carbon dots/metal–organic framework composite for ratiometric sensing of norfloxacin

Abstract: This fluorescent sensing material has the excellent optical properties of g-CDs and the selective detection and adsorption capability of UiO-66 for the target analyte; it determines the norfloxacin concentration via the F432/F530 fluorescence ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Interference arises because of the existence of several metal ions, including Fe 3+ , Ca 2+ , K + , Mg 2+ , and Cu 2+ , which can interfere with the NOR sensing capability inside a complex system. 14 Figure 4a depicts the precise identification of several ions and common biomolecules, such as NaCl, CaCl 2 , KCl, MgCO 3 , FeCl 3 , ZnNO 3 , urea, ascorbic acid, glucose, and glycine. The spectral study showed that the fluorescence sensor has specific sensitivity to NOR compared to other ions.…”
Section: Fluorescence Sensing Of Normentioning
confidence: 99%
“…Interference arises because of the existence of several metal ions, including Fe 3+ , Ca 2+ , K + , Mg 2+ , and Cu 2+ , which can interfere with the NOR sensing capability inside a complex system. 14 Figure 4a depicts the precise identification of several ions and common biomolecules, such as NaCl, CaCl 2 , KCl, MgCO 3 , FeCl 3 , ZnNO 3 , urea, ascorbic acid, glucose, and glycine. The spectral study showed that the fluorescence sensor has specific sensitivity to NOR compared to other ions.…”
Section: Fluorescence Sensing Of Normentioning
confidence: 99%
“…18 It can be served as a platform role to bind different fluorescent substances including organic dye molecules and quantum dots to fabricate dual-emission chemosensors. 19 Lanthanide metal organic frameworks have been extensively developed as the fluorescent probes owing to their excellent optical properties, and the abundant carboxyl groups on the surface of UiO-66-(COOH) 2 that can coordinate with lanthanide ions such as Eu 3+ , Tb 3+ , and Ce 3+ to exhibit characteristic luminescence via the antenna effect. 20 In this work, we propose the construction of a dual-emission ratiometric fluorescent nanoprobe for detecting HOCl based on Eu 3+ -modified and carbon dot-encapsulated MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As an emerging carbon nanomaterial, carbon dots (CDs) exhibit remarkable optical performance, which could emit fluorescence and phosphorescence with wavelength ranging from ultraviolet (UV) to near-infrared region. They also possess multiple advantages, including facile synthesis, ease of functionalization, , excellent biocompatibility, low toxicity, , and chemical stability. These characteristics endow them with extensive application potentials in the fields of optoelectronic devices, , energy storage, sensing, ,, and drug delivery. , Despite that impressive research, CDs are also widely utilized in the synthesis of composites.…”
Section: Introductionmentioning
confidence: 99%